Instytucjonalizacja, dezinstytucjonalizacja a zmiana społeczna - Malikowski, Marian (My University, 1991)
The article discusses the processes of institutionalization of social life in Poland and places them in a context of a social change. It starts with terminological problems, then it presents various platforms of the institutionalisation process, sketches the institutionalization process of social life with respect to public institutions appointed by the State and, finally, shows various possible institutional changes and their consequences. Main theses of the article are the following: 1. The institutionalisation process in the Polish People's Republic was political in character; it was aimed at authoritative regulation of its maximum range in a public sphere. It was subordinated to the interests of the authorities and it was meant to reinforce their position. 2. While public life was overly institutionalised, the institutions functioned inefficiently. At the same time some social needs did not find their institutional expression (e.g. political, economic and cultural needs). 3. At present, it is necessary to disinstitutionalise some spheres of social life (liquidation of many institutions, change of the existing institutions, creation of new institutions). 4. The above process may not be entirely spontaneous; some changes must be implemented by the State authorities.
Institutionalisation, Deinstitutionalisation and social change